2013
DOI: 10.1055/s-0032-1327395
|View full text |Cite
|
Sign up to set email alerts
|

Die Diagnose des Phäochromozytoms und Paraganglioms

Abstract: These results support use of the CST in combination with measurements of normetanephrine for confirming or excluding P/PGL in patients with borderline elevated test results, which should, however, first be confirmed by sampling blood under standardized resting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
2
0
1
Order By: Relevance
“…Applying these cutoffs, the diagnostic sensitivity and specificity were as high as 96% and 100%. Similar results were reported in a second study, 16 and these thresholds are currently recommended by an international guideline. 2 One of these studies included 97 patients (48 with and 49 without PPGL), but a high proportion of the PPGL patients had markedly elevated screening NMN (in whom the diagnosis of PPGL could have been established without CST).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Applying these cutoffs, the diagnostic sensitivity and specificity were as high as 96% and 100%. Similar results were reported in a second study, 16 and these thresholds are currently recommended by an international guideline. 2 One of these studies included 97 patients (48 with and 49 without PPGL), but a high proportion of the PPGL patients had markedly elevated screening NMN (in whom the diagnosis of PPGL could have been established without CST).…”
supporting
confidence: 89%
“…Our study revealed another interesting aspect. The normalization of plasma NMN at baseline sampling of the CST in more than half of the patients, which has also been observed in a smaller study, 16 suggests that repeated measurement of plasma MN and NMN with optimized preanalytics would be sufficient to exclude PPGL in a large proportion of patients. However, due to practical issues (eg, long distance to the specialized center, delayed availability of laboratory results), it can be reasonable to proceed occasionally directly to a CST.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our analysis highlights the fact, that in this setting use of for instance IA plus measurement of uMNs in 24-h urine collections as the initial diagnostic test procedure will yield a markedly higher rate of false positive results compared to blood sampling in the supine position plus measurement of pMNs with HPLC, and, even more important, the rate of false positive tests will remain considerably higher during any subsequent testing. Whether or not functional tests such as clonidine suppression [36,37] will aid in confirming the diagnosis under these circumstances is unknown. Therefore, proponents of the primary use of IA plus measurement of uMNs in 24-h urine collections for the biochemical diagnosis of P/PGL need to be aware of this potential trade–off and its continued impact on the further diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Werten im Grenzbereich kann zur Sicherung ein Clonidinsuppressionstest durchgeführt werden, der mit einer Sensitivität von 97 % und einer Spezifität von 100 % falsch positive von richtig positiven Befunden unterscheiden kann [17]. Auch die Bestimmung von Chromogranin A kann hilfreich sein [15].…”
Section: Merkeunclassified